Teachers’ Perception on Social Skills of Students with Visual Impairments and its Relation with Academic Achievements - Mohd Hafiz Baharom; Rosadah Abd Majid (Department of Special Education, 2017)
Social skills is one of the problems experienced by students with visual impairment due to the absence of visual perception. The aim of this study is to explore the level of social skills among students with visual impairment of teacher perception. This study also reviewed the level of academic achievement based on the result of Primary School Achievement Test (UPSR) and it’s correlation with the social skills. This survey was conducted on 32 year six students with visual impairment from special education integration program and Special Education School for The Blind from seven states. The instrument was a set of questionnaires that were administered to the sample teachers. Data were analysed using descriptive statistics which involved mean and standard deviation as well as inferential analysis Spearman’s correlation coefficient. The findings showed that teacher’s perception towards social skills of students with visual impairment was high. However, this survey also found that their level of academic achievement was low. Spearman’s correlation coefficient inference analysis revealed, there are positive but very weak and insignificant correlation between social skills and academic achievement. In conclusion, this study show efforts must be made in order to improve the academic achievement of these groups.Kemahiran sosial adalah salah satu permasalahan yang dialami oleh Murid Berkeperluan Pendidikan Khas (MBK) ketidakupayaan penglihatan akibat ketiadaan persepsi visual. Objektif kajian ini dijalankan adalah untuk meninjau tahap kemahiran sosial MBK ketidakupayaan penglihatan dari persepsi guru. Selain itu, kajian ini juga meninjau tahap pencapaian akademik MBK ketidakupayaan penglihatan melalui keputusan Ujian Pencapaian Sekolah Rendah (UPSR) dan melihat hubungannya dengan kemahiran sosial murid. Sampel kajian terdiri daripada 32 orang MBK ketidakupayaan penglihatan tahun enam program pendidikan khas integrasi dan Sekolah Pendidikan Khas Cacat Penglihatan dari tujuh buah negeri. Instrumen kajian ialah satu set borang soal selidik yang ditadbir ke atas guru yang mengajar sampel. Data dianalisis menggunakan statistik deskriptif yang melibatkan skor min dan sisihan piawai serta analisis inferensi Korelasi Spearman. Dapatan kajian menunjukkan persepsi guru terhadap kemahiran sosial MBK ketidakupayaan penglihatan tahun enam adalah tinggi. Selain itu, didapati pencapaian akademik MBK ketidakupayaan penglihatan adalah rendah. Analisis inferensi pekali Korelasi Spearman mendapati hubungan positif yang sangat lemah dan tidak signifikan antara kemahiran sosial dan pencapaian akademik. Dapatan kajian ini menjadi indikator kepada komuniti pendidikan khas ketidakupayaan penglihatan bahawa pelbagai usaha perlu dilakukan untuk memperbaiki pencapaian akademik golongan ini.DOI: http://dx.doi.org/10.17977/um029v4i12017p049